Gestational Tubal Choriocarcinoma Presenting as a Pregnancy of Unknown Location following Ovarian Induction. (3rd May 2018) - Lin, Lawrence Hsu; Fushida, Koji; Hase, Eliane Azeka; Schultz, Regina; Tenorio, Laysa Manatta; Madia, Fabricia Andrea Rosa; Zanardo, Evelin Aline; Kulikowski, Leslie Domenici; Francisco, Rossana Pulcineli Vieira
Abstract : The management of pregnancy of unknown location (PUL) can be a challenging situation, since it can present as several different conditions. Here we describe a rare case of gestational choriocarcinoma arising in the fallopian tube after ovarian induction in an infertile patient. The patient received clomiphene for ovarian induction and had rising levels of human chorionic gonadotropin (hCG) over nine months without sign of pregnancy. After referral to our center, the patient was diagnosed with a paraovarian tumor, which revealed a gestational choriocarcinoma arising in the fallopian tube; the final diagnosis was supported by pathological and cytogenomic analysis. Malignancies, such as gestational trophoblastic disease, should be in the differential diagnosis of PUL; the early recognition of these conditions is key for the proper treatment and favorable outcome.